Applications of Biochar for Environmental Safety 2020
DOI: 10.5772/intechopen.92611
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Biochar as a Soil Amendment to Reduce Potentially Toxic Metals (PTMs) Phytoavailability

Abstract: The contamination of potentially toxic metals (PTMs) is widespread in the world and has negatively affected plants, humans, soil health, and environmental quality. Some metals are essential plant nutrients but they are also toxic to vegetation and aquatic live when present in high concentrations, such as Cu, Mn and Zn. Others (e.g., Pb, Cd, Cr, and As) are potential toxic metals for all organisms, and are not needed (or are toxic) for plant growth. This chapter summarizes the use of readily available biochars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The maximum effect on the heavy metal concentration was observed when biochar was applied at the B3 (9%), followed by B1 (3%) and B2 (6%) (Table 1). In agreement with our results, many previous studies have reported that biochar application significantly increases the immobilization of heavy metals in soils as well as reduces their bioavailability for plant uptake (Kim et al 2015; Dang et al 2015; Liu et al 2020; Antonangelo & Zhang, 2020). These studies have demonstrated that the biochar interacts with the heavy metals in the soil, thus the ions of heavy metals are adsorbed on the pore surfaces, and transformed into the carbonate, hydroxide, and phosphate precipitates.…”
Section: Resultssupporting
confidence: 93%
“…The maximum effect on the heavy metal concentration was observed when biochar was applied at the B3 (9%), followed by B1 (3%) and B2 (6%) (Table 1). In agreement with our results, many previous studies have reported that biochar application significantly increases the immobilization of heavy metals in soils as well as reduces their bioavailability for plant uptake (Kim et al 2015; Dang et al 2015; Liu et al 2020; Antonangelo & Zhang, 2020). These studies have demonstrated that the biochar interacts with the heavy metals in the soil, thus the ions of heavy metals are adsorbed on the pore surfaces, and transformed into the carbonate, hydroxide, and phosphate precipitates.…”
Section: Resultssupporting
confidence: 93%
“…But challenges remain in terms of practicality, effectiveness, cost and sustainability at large-scale field application at commercial levels. Large-scale field trials are essential before implementation of operational scale remediation projects Antonangelo and Zhang, 2020). One of the key challenges associated with large-scale filed trials is to achieve comparable or better remediation results compared to smallscale experiments considering the prevailing real-world environmental parameters.…”
Section: Remediation Mechanism Of Biocharmentioning
confidence: 99%
“…The greatest concern of organic contaminants such as pesticides, herbicides, polycyclic aromatic hydrocarbons, dyes, and antibiotics have been a concern due to its toxicity and accumulative properties [38]. In the soil medium, biochar has been used for heavy metal sequestration [39,40]. In this process, heavy metals are immobilised not removed and maybe converted into hydroxide, carbonate, and phosphate precipitates [40].…”
Section: Role Of Biochar In Pollution Managementmentioning
confidence: 99%
“…Properties of biochar such carbonaceous materials, degree of aromatization, elemental composition, pH, pore structure, surface chemistry, etc., plays vital roles in its ability to adsorb organic pollutants [41]. Biochar therefore reduces CO 2 emissions into the atmosphere [39]. The indiscriminate exploitation of natural resources and the rapid growth of environmental destruction resulting from anthropogenic activities have already posed a burden on efforts to sustain natural environment.…”
Section: Role Of Biochar In Pollution Managementmentioning
confidence: 99%
See 1 more Smart Citation